(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
تخفيض تكاليف التخزين بأستخدام المصابيح الاقتصادية (دراسة ميدانية في مجمع مخازن ديالى ) Different kind of organization afford many costs such as storage .storage is a function of preserving materials till needed .storage costs include demand costs ,preserving the stored materials costs ,expire costs, and in addition to lighting costs used in stores either in offices or in storage locations costs are expensive in usual. The research problem is revealed the highly cost of in stalling electric sets and equipments related to lighting the highly costs of lamps and their maintaining expensively ,also the highly costs of electric power fees whether the Public or the use of stores, electric generators all lead to increase the costs of storage and put the additional cost upon units .Thereby the importance of the research appears, when costs become huge amounts and load on storage process.